The Development of Electronic Students’ Worksheets (E-LKPD) Based on Argument Driven Inquiry Learning Model to Improve Scientific Argumentation Skills - Utami, Suri Margi; Haryanto, Haryanto; Subagyo, Agus (Integrated Science Education Journal, 2024)
Purpose of the study: This research aims to develop electronic student worksheets (E-LKPD) based on the Argument Driven Inquiry (ADI) Model to enhance the scientific argumentation skills of high school students. The impetus for innovative educational tools is intensified by ongoing industrial and social revolutions, necessitating advanced human resource capabilities. Methodology: Research and development, the study encompasses the stages of analysis, design, development, implementation, and evaluation. The subjects were 29 Class XI IPA students. Data analysis utilized descriptive statistics and paired sample t-tests to assess the effectiveness of the E-LKPD in improving students' argumentation skills. Main findings: Validation results from material and media experts indicated that the E-LKPD is highly feasible. Furthermore, responses from science teachers and student trials in one-on-one, small, and large group settings rated the E-LKPD in the "very good" category. A notable finding was the significant improvement in students' argumentation skills when using the E-LKPD, as evidenced by the paired sample t-tests. Novelty/Originality of this study: The originality of this study lies in its application of the ADI model to E-LKPD, tailored to meet the demands of the industrial and social revolutions by fostering an entrepreneurial mindset in students. This research underscores the critical need for educational innovation, particularly in integrating entrepreneurship-based learning videos in junior high schools. By instilling an entrepreneurial spirit, students are better equipped to navigate and compete in the contemporary landscape, making this study a pivotal contribution to educational practices and resource development.